Deformation mechanisms of TRIP–TWIP medium-entropy alloys via molecular dynamics simulations. (1st April 2022) - Pan, Zhimin; Fu, Yu; Wei, Ya; Yan, Xiongbo; Luo, Hong; Li, Xiaogang
Highlights: Less Shockley partial dislocations (SPDs) are observed as the grain size decreases, which may be due to the transformation from intragranular to intergranular evolutionary mechanisms within a nanoscale range. Stacking faults are markedly suppressed as the average grain size decreases. The interaction of cluster defects with the SPDs produces a promoting effect on the nucleation of stacking faults. Dislocation nucleation rate seems to be increased as a linear relationship following the increase in the grain sizes. Abstract: Medium/high-entropy alloys (MEAs/HEAs) have become one of the primary research highlights in the material field due to their superior microstructure and mechanical properties. By means of molecular dynamic (MD) simulation, the tensile behavior of polycrystalline Fe80-x Mnx Co10 Cr10 (x=20, 30, 40, 50) MEAs was investigated under uniaxial stretching. The effects of various strain rates (1 × 10 8 s −1, 1 × 10 9 s −1, 1 × 10 10 s −1 ) and deformation temperatures (77 K, 300 K, 600 K, 800 K) on tensile properties and deformation mechanisms of Fe80-x Mnx Co10 Cr10 (x=30, 40) MEAs were explored, and the interaction of dislocation defects with stacking fault including intrinsic and extrinsic stacking fault (ISF/ESF) as well as the evolution of dislocation and cluster defects were further discussed. Moreover, the relationship between grain size and flow stress of polycrystalline Fe50 Mn30 Co10 Cr10 MEAs was discussed. Results indicated that Fe40 Mn40 Co10 Cr10 and Fe50 Mn30 Co10 Cr10 alloys exhibited higher yield stresses and Young's moduli. The yield stresses, Young's moduli and average flow stresses of Fe40 Mn40 Co10 Cr10 and Fe50 Mn30 Co10 Cr10 MEAs increased with an increase in strain rates from 1 × 10 8 to 1 × 10 10 s −1 . Besides, the deformation temperature produced a considerable influence on its mechanical properties. The phase transformation, grain boundary glide, dislocation slip and twinning formation together accounted for the plastic deformation behavior of Fe80-x Mnx Co10 Cr10 MEAs under uniaxial stretching on an atomic scale. Graphical abstract: Image, graphical abstract